THE USE OF JIGSAW TECHNIQUE IN IMPROVING STUDENTS' ACHIEVEMENT IN READING EXPOSITION TEXT:A Quasi-Experimental Study to the Second Grade Students of A Senior High School in Cimahi - Riswita Anjang Sari, - (2012)
This study raises an issue about teaching reading. Reading skill is very important for EFL students in language learning mastery, therefore, a good and interesting technique for teaching reading is necessary to improve students' reading comprehension. Nowadays, some teachers still use conventional technique in teaching reading. However, the conventional technique does not seem to motivate the students and make a significant progress. That is why Jigsaw technique is proposed as the alternative way to improve students' reading comprehension. The aim of the study was to investigate whether or not Jigsaw technique was effective in improving students' reading comprehension and to investigate the students' responses towards the use of Jigsaw technique in teaching reading. The study used quasi-experimental design with pre-test and post-test design. The study involved two classes of the second grade students of a public senior high school in Cimahi as the sample. Jigsaw technique was effective in improving students' reading comprehension. The findings from the questionnaires showed that almost all students were interested in Jigsaw technique. The students agreed that Jigsaw technique increase their reading skill, increase their motivation and enthusiasm, develop their communication and social skills. The findings from the post-test of the experimental and control groups indicated that Jigsaw technique treatment was significantly effective in improving students' reading comprehension. It can be seen from the statistical result of post-test score of experimental group (M = 8.41, SE = 0.17) that was higher than control group (M = 7.18, SE = 0.21). Since the probability of dependent t-test was less than α; t (58) = -22.564, p < 0.05, so H0 was rejected. It means that there was difference between experimental and control groups. In reference to the result of the study, the conclusion was drawn that Jigsaw technique treatment significantly improved the second grade students' reading comprehension. As recommendation, teachers who apply this technique should use Jigsaw technique along with clear instructions.